Cumulative effect of AOC1 gene variants on symptoms and pathological conditions in adult women with fibromyalgia: a pilot study - Okutan, Gülşah; Perucho Alcalde, Teresa; Ruiz Casares, Eva; Penadés, Bruno F.; Sánchez Niño, Guerthy Melissa; Terrén Lora, Ana; López Oliva, Sara; Torrente Estríngana, Lorena; Duelo, Adriana; San Mauro Martín, Ismael (Frontiers in Genetics, 2023)
Introduction: The Amine Oxidase Copper Containing 1 (AOC1) gene encodes for the diamine oxidase (DAO) enzyme. DAO is an enzyme that catabolizes some molecules, including histamine, and is the degradative enzyme in the polyamine catabolic pathway that is active in intestinal mucosal cells. Variants of the AOC1 are associated with reduced DAO activity, resulting in the accumulation of high levels of histamine and causing a wide range of neurological, gastrointestinal, and epidermal disorders, which are present in people with fibromyalgia. This study aimed to evaluate the impact of four AOC1 gene variants, namely rs10156191, rs1049742, rs1049793, and rs2052129, on fibromyalgia symptoms measured by the Fibromyalgia Impact Questionnaire (FIQ), such as sleep disorders, atopic dermatitis, migraine, gastrointestinal (GI) disorders, allergies, and intolerances in adult women with fibromyalgia. Methods: The sample consisted of 100 unrelated women with fibromyalgia between 33 and 60 years of age (48.48 years ± 7.35), whose diagnosis was made by a rheumatologist based on symptoms such as pain, stiffness and fatigue. Single nucleotide polymorphisms (SNPs) of the AOC1 were identified using oral mucosa samples collected following a standard hygiene protocol. DNA was extracted, and gene variants of interest were analyzed using multiplex single nucleotide primer extension (SNPE). The collection of clinical data was carried out using the FIQ and a series of variables that quantified the intensity and frequency of the symptoms. Results: The minor allele frequencies of rs10156191, rs1049742, rs1049793, and rs2052129 were 31.5, 10, 32.5, and 27%, respectively. Each variant was found to be in Hardy-Weinberg's equilibrium, but a partial linkage disequilibrium between AOC1 SNPs is suspected. The results show that fibromyalgia symptoms measured using the FIQ tend to increase with the number of risk alleles and that the intensity of dry skin and low stool consistency may be associated with an increase in the number of these alleles. Conclusions: This study constitutes the first step in investigating associations between fibromyalgia symptoms and candidate variants of the AOC1 gene in DAO enzyme activity. Identification of reduced DAO activity may improve the quality of life and treatment of symptoms in fibromyalgia patients.